Booker T. Washington and the Struggle against White Supremacy - Jackson, D. author. aut Link
XVIII, 260 p. 10 illus.
Keywords: This book narrates and analyzes the southern tours that Booker T. Washington and his associates undertook in 1908-1912, relating them to Washington's racial philosophy and its impact on the various parts of black society.